2017
DOI: 10.3389/fnins.2017.00523
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Clinical Pathway and Technical Aspects of Upper Airway Stimulation Therapy for Obstructive Sleep Apnea

Abstract: Obstructive sleep apnea (OSA) is a common disease with high morbidity and related mortality. Narrowing and collapse of the pharyngeal airway during sleep characterize the disease, resulting in a decrease (hypopnea) or a complete cessation (apnea) of oronasal airflow. Upper airway stimulation (UAS), using electrical neurostimulation of the hypoglossal nerve (n. XII) synchronized with ventilation, is a novel, evolving treatment option. UAS was found to be an effective treatment in CPAP-intolerant patients. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
55
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 74 publications
0
55
0
2
Order By: Relevance
“…We believe that the range of improvement shown in this proof of concept study will be increased both by refining the stimulation technique itself and also by a prospective identification of responder’s profile as it has been done for hypoglossal stimulation 9,19 . Indeed, in this study, we retrospectively labelled patients as ‘responders’ when they presented a statistically significant decrease in terms of event duration for either apnea or hypopnea events.…”
Section: Discussionmentioning
confidence: 92%
“…We believe that the range of improvement shown in this proof of concept study will be increased both by refining the stimulation technique itself and also by a prospective identification of responder’s profile as it has been done for hypoglossal stimulation 9,19 . Indeed, in this study, we retrospectively labelled patients as ‘responders’ when they presented a statistically significant decrease in terms of event duration for either apnea or hypopnea events.…”
Section: Discussionmentioning
confidence: 92%
“…The overall response to kinesthetic stimulation was significant but clinical relevance of the size effect can be discussed. We believe that the range of improvement shown in this proof of concept study will be increased both by refining the stimulation technique itself and also by a prospective identification of responder's profile as it has been done for hypoglossal stimulation 9,19 . Indeed, in this study, we retrospectively labelled patients as 'responders' when they presented a statistically significant decrease in terms of event duration for either apnea or hypopnea events.…”
Section: Discussionmentioning
confidence: 92%
“…A complete concentric collapse at the level of the palate (CCCp), as observed during DISE, has been a reported predictor for decreased success rate of some specific non‐CPAP treatment options such as UA stimulation, UA surgery, and MAD . Specifically, surgical treatment with UA stimulation, using electrical neurostimulation of the hypoglossal nerve synchronized with ventilation, fails to reduce OSA severity in patients with CCCp . Consequently, according to the Food and Drug Administration approval statement, CCCp became a formal exclusion criterion for UA stimulation therapy …”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Specifically, surgical treatment with UA stimulation, using electrical neurostimulation of the hypoglossal nerve synchronized with ventilation, fails to reduce OSA severity in patients with CCCp. 15,16,19 Consequently, according to the Food and Drug Administration approval statement, CCCp became a formal exclusion criterion for UA stimulation therapy. 15,16 The aim of the present prospective study was to evaluate the effect of UA collapse patterns as observed during DISE on MMA surgery outcome, with particular attention to the effect of a preexisting CCCp DISE phenotype.…”
Section: Introductionmentioning
confidence: 99%